2015
DOI: 10.1515/amm-2015-0238
|View full text |Cite
|
Sign up to set email alerts
|

Structural And Optical Properties Of VOx Thin Films

Abstract: VO x thin films were deposited on Corning glass, fused silica and Ti foils by means of rf reactive sputtering from a metallic vanadium target. Argon-oxygen gas mixtures of different compositions controlled by the flow rates were used for sputtering. Influence of the oxygen partial pressure in the sputtering chamber on the structural and optical properties of thin films has been investigated.Structural properties of as-sputtered thin films were studied by X-ray diffraction at glancing incidence, GIXD. Optical t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
0
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 27 publications
1
0
0
Order By: Relevance
“…X-ray analysis confirmed that all peaks correspond to the V 2 O 5 orthorhombic phase. The results are well agreed with those obtained by Zhang et al[4], Fu et al ]13] and Schneider[16]. The diffraction peaks of the samples manifest that the samples were well crystallized and correspond to the JCPDS Card numbering 41-1426.…”
supporting
confidence: 90%
“…X-ray analysis confirmed that all peaks correspond to the V 2 O 5 orthorhombic phase. The results are well agreed with those obtained by Zhang et al[4], Fu et al ]13] and Schneider[16]. The diffraction peaks of the samples manifest that the samples were well crystallized and correspond to the JCPDS Card numbering 41-1426.…”
supporting
confidence: 90%